Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai di Dinas Perhubungan Kota Samarinda - Julianty Wulandari Maskan dan Frendly Albertus (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2018)
This study aims to determine the Influence of Organizational Culture onEmployee Performance At Department of Transportation in Samarinda City.The result of the research shows that there is a positive andsiginificant correlation between Organizational Culture variable withEmployee Performance at Department of Transportations in Samarinda City.Another thing can be known from the result of statistical test KoefisienKorelasi Product Moment the result is r = 0,504 which means there is astrong and positive relationship between the two variables.Meanwhile, t test result ( table coefficients) obtained t value counted= 4,038. While the table statistics (ttabel) obtained from table t ( attached) for= 1,677 means t count > t table ( 4,038 > 1,677 ). So it can be concluded that,the independent variable Organizational Culture has a positive and sinificantrelationship to Employee Perfomance. Thus it can be said also that thepurpose of this study can be achieved, the problem can be solved and thehypothesis can be proven.